Top Mysteries of the Mind: Insights From the Default Space Model of Consciousness - Jerath, Ravinder; Beveridge, Connor (Frontiers in Human Neuroscience, 2018)
Aside from the nature of consciousness itself, there are still many unsolved problems in the neurosciences. Despite the vast and quickly growing body of work in this field, we still find ourselves perplexed at seemingly simple qualities of our mental being such as why we need to sleep. The neurosciences are at least beginning to take a hold on these mysteries and are working toward solving them. We hold a perspective that metastable consciousness models, specifically the Default Space model, provide insights into these mysteries. In this article, we explore some of these curious questions in order to elucidate the interesting points they bring up. The Default space model is a dynamic, global theory of consciousness that involves the maintenance of an internal, 3D simulation of the external, physical world which is the foundation and structure of consciousness. This space is created and filled by multiple frequencies of membrane potential oscillations throughout the brain and body which are organized, synchronized, and harmonized by the thalamus. The veracity of the Default Space model is highlighted here in its ability to further understanding of some of the most puzzling problems in neuroscience.